Final pass and its relationship with final action for the creation of goal-scoring opportunities at EURO 2020 - Kyranoudis, E.; Papadimitriou, K.; Kyranoudis, A.; Giannakopoulos, A.; Konstantinidou, X. (Journal of Human Sport & Exercise, 2024)
The purpose of this research was to study EURO 2020 goal scoring opportunities by recording the technique of the final pass, the technique of the final action and their zone of execution. A sub-objective was to test the relationship between the technique and zone of the final-pass, but also the relationship between the final-pass zone, the zone of final-action and its efficiency. The parameters studied were, a) the final pass zone, b) the final pass technique, c) the final action zone, and d) the result of the final action. Data collection was done with SportScout software. The correlation between variables was tested using the Crosstabs analysis and the Chi-Square statistic criterion. The results showed that most of the final passes were made from the zone outside the 18-yard box and the most common techniques used were the medium-range and the short-range passes. The independence or homogeneity test showed that the type of final pass was significantly influenced by the zone in which it was executed. The same was the case with the final action zone, which appeared to be significantly affected by the final pass zone. However, the effectiveness of the attacks depended only on the zone of final action (the final actions were more effective when taken from the zone between the six-yard box area and the penalty spot). An assessment of the opportunities that lead to goals and how they are created can help identify the tactical factors that increase efficiency and lead to more goals being scored.